2018
DOI: 10.1111/cen.13791
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of a large prospective cohort of patients with nonfunctioning pituitary adenomas: The outcome of a conservative management policy

Abstract: This study suggests that a conservative approach may be safe and appropriate in patients with NFPA if followed up with appropriate imaging surveillance, whether postoperative or without primary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…Follow-up showed a low rate of recurrence in our NFPA series, in accordance with the majority of reported studies [11,29,30], though not all [31][32][33][34], with or without radiotherapy. A meta-analysis reported a 2-fold higher risk of recurrence without radiotherapy compared to radiotherapy of NFPA [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Follow-up showed a low rate of recurrence in our NFPA series, in accordance with the majority of reported studies [11,29,30], though not all [31][32][33][34], with or without radiotherapy. A meta-analysis reported a 2-fold higher risk of recurrence without radiotherapy compared to radiotherapy of NFPA [32].…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis reported a 2-fold higher risk of recurrence without radiotherapy compared to radiotherapy of NFPA [32]. A long term follow-up survey of 190 cases of NFPA has reported a 25 % recurrence rate at 10 years, in those with no residual tumor after pituitary surgery, increasing to a 60 % recurrence rate in the case of post-surgical intrasellar residuum [33]. Recently, Lelotte et al reported a series of 120 NFPA macroadenomas retrospectively evaluated for clinical outcomes and found 5-year recurrence of between 20 and 66 % depending on their initial proliferative and invasive status [34].…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Longterm outcomes following EES for pituitary adenomas have shown recurrence rates up to 10.7%-25.0% (Table 9). 3,22,37 Dallapiazza et al and Levy et al reported rates of 20% and 25%, respectively, according to the 10-year Kaplan-Meier estimate. Our study, which established extent of resection with postoperative MRI, revealed a much lower 10-year recurrence rate of 4.7%.…”
Section: Fig 3 Predictors Of Recurrence/progression-free Survival In the Entire Cohort (A-c) And Predictors Of Progression-free Survival mentioning
confidence: 97%
“…Arising from adenohypophyseal cells, these masses present either incidentally on imaging or via symptoms secondary to cranial mass such as headache, pituitary dysfunction, or visual disturbances. Therapy in way of hormonal replacement and/or surgical management via transsphenoidal approach is directed at correcting hypopituitarism or eliminating mass effect on adjacent neural structures, respectively [27]. Despite the availability of therapeutic modalities to treat NFPAs, the genetic mechanisms that lead to the initiation of NFPAs remain incompletely understood, particularly as pertaining to SNPs.…”
Section: Snps In Nonfunctional Pituitary Adenomasmentioning
confidence: 99%